Recent advances in biopolymeric composite materials: Future sustainability of bone-implant. (October 2021) - Oladapo, Bankole I.; Zahedi, S. Abolfazl; Ismail, Sikiru O.; Olawade, David B.
Abstract: Direct structural and purposeful relation between bone and implant is known as osteointegration. When an implant is inserted into the bone, a bone-implant interface is created, a critical area between the surface of implanted biomaterial and the surrounding bone. This research aimed to summarise the outcome of a crucial review conducted on poly-ether-ether-ketone (PEEK) and its composite materials, such as cellular calcium hydroxyapatite (cHAp) for medical applications. The prospective medical implant interface of PEEK was studied. Also, critical analysis and review on 3D printing of PEEK, its composites and natural macromolecular behaviour interface healing process for a bone implant are highlighted. Scopus database was used for electronic and Google search, and peer-reviewed papers in the last twelve years were studied. The study further includes a novel classification of polymer PEEK, the mechanical strength involved during the regeneration process of bone tissues. Due to the extraordinary power of the PEEK, its composites and their excellent natural behaviour, critical PEEK 3D printability research was reported for various biomedical applications and its natural health sustainable behaviours. In addition, the effectiveness and efficiency of the implant interface of PEEK depend on the natural conditions of the bone, design characteristics of implant and distribution of loads between bone and implant. Also explained, are the ideal options to boost 3D printability and scientific mechanisms of PEEK composites. This detailed review would benefit the scientific and medical community to enhance sustainability. Lastly, the description of the bone-implant interface reported within this compendious review can be used to determine the most relevant characteristics to consider in formulating models for osteointegration of bone-implants. Highlights: To summarise the outcome of a crucial review PEEK and its composite materials in nature sustainability. A novel classification of polymer PEEK, the mechanical strength in regeneration process of bone tissues. Current printing problems, and potential applications of 3D printing of PEEK in the medical implants. Study proposes a state-of-the-art and analytical review on the 3D printing of PEEK and its composite. Ideas, feasible solutions, and enabling scientific mechanisms to improve the 3D printability of PEEK/HAp.